Quality Improvement Analysis for MyIndiHome Application Using Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) Method - Yusrah Ubaid Salim (Jurnal Administrasi Bisnis, 2017)
MyIndiHome is digital product in the form of an application from PT Telkom Indonesia which is used to help and facilitate consumers to get services from IndiHome products. Achievement of more than one million installers, myIndiHome application has a low rating, which only gets 3.1 on Google Play and 2.1 on Apps Store. This is caused by many application users who are not satisfied and their needs are not well accommodated with the application. Therefore, companies need to improve service quality on it. This study aims to determine the attributes of customer needs, the technical characteristics from the company and the finale result is recommendations. This research uses a mixed method by distributing questionnaires about 80 people as online and 20 people as offline to myIndiHome application users and do some good discussion activities with Telkom Digital Service Division employees. The variables used in this study are digital product and e-service quality that will be processed using the Importance Performance Analysis (IPA) methods and Quality Function Deployment (QFD) methods. The results of this research show that there are six attributes of consumer needs and 10 attributes of technical characteristics that will be formulated as recommendations for improvement.